Material Practice and Materiality: Too Long Ignored in Science Education - Milne, Catherine; Scantlebury, Kathryn; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
In this book various scholars explore the material in science and science education and its role in scientific practice, such as those practices that are key to the curriculum focuses of science education programs in a number of countries. As a construct, culture can be understood as material and social practice. This definition is useful for informing researchers' nuanced explorations of the nature of science and inclusive decisions about the practice of science education (Sewell, 1999). As fields of material social practice and worlds of meaning, cultures are contradictory, contested, and weakly bounded. The notion of culture as material social practices leads researchers to accept that material practice is as important as conceptual development (social practice). However, in education and science education there is a tendency to ignore material practice and to focus on social practice with language as the arbiter of such social practice. Often material practice, such as those associated with scientific instruments and other apparatus, is ignored with instruments understood as "inscription devices", conduits for language rather than sources of material culture in which scientists share (3z(Bmaterial other than words(3y (B(Baird, 2004, p. 7) when they communicate new knowledge and realities. While we do not ignore the role of language in science, we agree with Barad (2003) that perhaps language has too much power and with that power there seems a concomitant loss of interest in exploring how matter and machines (instruments) contribute to both ontology and epistemology in science and science education. .s
Introduction: Bringing Matter into Science Education, Kathryn Scantlebury & Catherine Milne -- Different Perspectives on Materials -- Thinking about practices differently: Why materials matter, Catherine Milne -- The materiality of materials and artefacts used in science classrooms, Kathrin Otrel-Cass & Browen Cowie -- How Spacetimemattering Engages Science Education with Matter, Kathryn Scantlebury, Anna Danielsson, Anita Hussenius, Kristina Andersson, & Annica Gullberg -- The Ethical, Political Potential of New Materialisms For Science Education, Shakhnoza Kayumova & Jesse Bazzul -- Curriculum Matters -- Positing an(other) ontology: Towards different practices of ethical accountability within multicultural science education, Marc Higgins -- Intra-actions that matter: building for practice in a Liberal Arts science course, Catherine Milne -- How does matter matter in preschool science? Sofie Areljung -- Classroom Matters -- New materialisms and science classrooms: diagramming ontologies and critical assemblies, Jesse Bazzul, Sara Tolbert & Shakhnoza Kayumova -- Agency, materiality, and relations in intra-action in a kindergarten science investigation, Jana Maria Haus & Christina Siry -- From lab to lecture: science teachers$1 (Bexperiences translating the materiality of lab-based research experiences into classroom practice, Nancy Morabito -- Technoscience Matters -- Socio-material relations in asynchronous learning environments, Shannon M. Burcks Marcelle A. Siegel, Christopher D. Murakami, Tamara Hancock, Rose Marra -- Affordances offered by the material nature of a website designed for teacher learning, Paul Davies & Shirley Simon -- Teachers as participatory designers of a professional development website, Shirley Simon, Paul Davies -- Learning matter: The force of educational technologies in cultural ecologies, Cathrine Hasse -- Ending Matters -- Communicating through silence: examining the unspoken and the unsaid in discussions about science, Kathryn Scantlebury, Anna Danielsson, Anita Hussenius, Kristina Andersson, & Annica Gullberg -- Conclusion: Telling us what to do. Moving on in a material world, Catherine Milne & Kathryn Scantlebury.s
Keywords: Science education; Educational sociology; Education$1 (BPhilosophy.s; Cultural studies; Learning; Instruction; Science Education; Sociology of Education; Educational Philosophy; Cultural Studies; Learning & Instruction